Penegakan Etika dan Tanggung Jawab Profesi Advokat Dalam Kasus Dugaan Obstruction of Justice Oleh Roy Renin - Aristias, Adinda; Lewoleba, Kayus Kayowuan (Media Hukum Indonesia (MHI), 2025)
As one of the pillars of law enforcement, the legal profession of advocacy carries a significant ethical responsibility to uphold justice and maintain the integrity of the judicial system. However, in practice, ethical violations by advocates still occur, including actions that may constitute obstruction of justice. This article aims to analyze the forms of ethical responsibility inherent in the legal profession and evaluate the challenges in enforcing the code of ethics, using the case of alleged obstruction of a corruption investigation by advocate Roy Rening in the Lukas Enembe case. This study employs a normative juridical method with a case study approach. The findings indicate that breaches of ethical boundaries by advocates can undermine public trust and weaken the profession's integrity. Furthermore, the enforcement of ethical codes in Indonesia faces structural and cultural obstacles, such as weak internal oversight, fragmentation among professional organizations, and resistance to accountability. Therefore, reforms are needed to establish a more independent, assertive, and harmonized ethical enforcement mechanism across advocate organizations to strengthen professional accountability and preserve the honor of advocacy as an officium nobile